A QoS-Assured and Mobility-Aware Routing Protocol for MANETs - Seyedakbar Mostafavi; Vesal Hakami; Fahimeh Paydar (Society of Visual Informatics, 2020)
In Mobile Ad Hoc Networks (MANETs), lack of a fixed infrastructure, dynamic network topology, device mobility and data communication over wireless channels make the multi-hop routing a very challenging task. Due to mission-critical applications of MANET, dealing with these challenges through the design of a Quality of Service (QoS)-assured protocol is a substantial problem. Mobility in MANETs is commonly considered as a negative factor on quality, although we suggest that the right approach to mobility awareness using wisely selected metrics can lead to a robust and QoS-assured protocol. In this paper, we propose QMAR-AODV, a QoS-assured Mobility-Aware Routing protocol which is an optimized version of AODV protocol. We utilize a combination of stability and quality metrics including Mobility Ratio (MR(C,E)) between nodes in a route, Energy Efficiency and congestion load to choose the most stable and QoS-assured routes. Our simulation results show that QMAR-AODV protocol outperforms E2E-LREEMR and reduces route instability, end-to-end delay, data retransmissions and packet loss by 8.3% 10.9% 10.6% and 5.4 respectively, while increases data reception and network throughput by 5.1% and 4.8% respectively, compared to E2E-LREEMR routing protocol.